Odpowiedzi

2010-01-21T21:54:11+01:00
Zad1
a) 3
b) 2x
c) 2pq
d) (3a+2b)
e) (2p-r)
f) (x-1/4y)
g) (1/3a-b)
h) (x+y+1/5)
i) (3d-1/2)
j) (2b-4a)

zad2
a) 2y-3xy
-2x²+3x³
x-3/2x²

b)5-ab
-b²+1/5ab³
ab-1/5a²b²

zad3
a) 196(295-296)=196*(-1)=-196
b) 2,8(8,2+1,8)=2,8*10=28
c) 149,9+149,9*8-1499=149,9+149,9*8-149,9*10=
149,9(1+8-10)=149,9*(-1)=-149,9
d)14i1/21(8/17+9/17)= 14i1/21*17/17= 14i1/21*1= 14i1/21
e) 1/2664+23/2664=24/1664=1/111
f) 7³+7
-----------=
7²+1

7(7²+1)
-------------=
7²+1

po skróceniu daje to 7

zad4
a) (x²+x+1)
b) [x²+(1-x)+(x+1)]= (x²+1-x+x+1)